PENGARUH PENDEKATAN SAINTIFIK BERBANTUAN MEDIA KORAN TERHADAP HASIL BELAJAR DAN AKTIVITAS PESERTA DIDIK PADA SUB MATERI PENCEMARAN LINGKUNGAN SMA - Supriyadi, Arif; Ningsih, Kurnia; Ariyati, Eka (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
The research aimed to find out the effect of scientific approach using newspaper on student achievement and student activity on environmental pollution material ingrade X Senior High School Muhammadiyah 1 Pontianak. This was a quasi experimental study using nonequivalent control group design. The samples of the research were grade X MIA 1 as an experimental group,Â  andgrade XÂ  MIA 2 as ancontrolgroup. The instrument employed was multiple choice test consisting 20 question and observation sheet of student activity. The average score for student achievement on experimental group was 14,86 and 13,29 for control group. Based on Mann Whitney U test for Zcount(-2,42) < -Ztabel(-1,96), there was a significant difference between student achievement that used newspaper and picture those who did not use these media. The effect size score was 0,67 (moderate) gave effec tby 24,82%. Student activity on experimental group improvedby 7,41% and 4,29% for control group. It is shown that scientific approach using newspaper had an impact on student achievement and student activity on environmental pollution material ingrade X Senior High School Muhammadiyah 1 Pontianak. Keywords: activity, learningoutcome, newspaper, scientific.